S08-1: Mapping Established Monitoring Tools for National Physical Activity Policies: Insights and Implications (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: As the importance of public policies to promote physical activity (PA) is increasingly recognised, several tools have been developed to monitor and evaluate these policies. Previous research has highlighted that different tools have been developed for different purposes; however, there is limited guidance about the similarities and differences of these tools and their respective roles in the policy context. This study aims to map existing international monitoring tools for national-level PA policies and to explore their impact on the policy process.Methods: Physical activity policy monitoring tools for the national level were identified based on existing systematic reviews and manual searches of the scientific literature. The tools were analysed in a comparative desk-based mapping exercise, incorporating a political science perspective. Semi-structured expert interviews were conducted to gain additional insight into the development and use of these tools.Results: Eight tools were identified, developed by the World Health Organisation (e.g. Global Action Plan on PA Monitoring Framework), the European Union (e.g. EU Health Enhancing PA Monitoring Framework), and researchers. The mapping of indicators showed that these tools collect different data on policy content (e.g. the promotion of cycling), the policy process (e.g. policy implementation), and the political structure (e.g. platforms for intersectoral collaboration). The expert interviews revealed success stories of the real-world impact of these tools on the policy process as well as current challenges.Conclusions: This study has identified similarities and differences in existing monitoring tools for PA promotion. While a variety of tools with different objectives and methodologies may have advantages from a scientific perspective, a fragmented landscape could limit the impact of physical activity policy monitoring on the policy process. Lessons can be drawn from the field of political science, where scholars have analysed the use of policy monitoring and evaluation from a more general perspective.Support/Funding Source: Funded by the European Union under Horizon Europe’s Marie Skłodowska-Curie Actions (MSCA), grant agreement ID 101109929. Views and opinions expressed are however those of the author(s) only and do not necessarily reflect those of the European Union or the European Research Executive Agency (REA). Neither the European Union nor the granting authority can be held responsible for them.